Kinetic Decomposition Models for Ammonium Percholorate Hybrid Catalyzed with Nanothermite Particles. Issue 1 (1st August 2022) - Hamed, Abdelaziz; Gobara, Mohamed; Mokhtar, Mohamed; Elbasuney, Sherif
Abstract: Ferric oxide is a universal catalyst. Reactive metal fuel can act as a high energy dense material such as aluminum which is marked by the very high gravimetric and volumetric heat output. This manuscript reports on the fabrication of colloidal ferric oxide nanoparticles of 5 nm. Colloidal ferric oxide/aluminum nanothermite mixture was integrated into ammonium percholorate (AP) via the coprecipitation technique. The shape and particles size of the prepared nano ferric oxide were investigated by using TEM instrument. Uniform dispersion of Al/Fe2O3 in the ammonium perchlorate matrix was verified using EDAX instrument. Nanothermite particles offered enhanced AP decomposition enthalpy by 120 % using DSC. Nanothermite colloid offered a decrease in AP activation energy by 51 and 40 % using Friedman and Ozawa models respectively. AP decomposition mechanism was reported to go through three consequent mechanisms including the first order mechanism, two-dimensional diffusion reactions, and one- dimensional diffusion mechanism according to extent of reacted fraction (α) of 0-0.25, 0.3-0.6, and 0.6-0.9 respectively. The results show that the catalyzing ability of the nanothermites was confirmed and has shown a superior effect on the AP energetic system.